ANALISIS PEMBIAYAAN PEREMAJAAN KAWASAN PERMUKIMAN DI PUSAT KOTA DENGAN MODIFIKASI CONTINGENT VALUATION METHOD - , Viveri
The Local Government of Sawahlunto has intended to develop tourism sector as one of the source of income, because there is a gap in the development of coal mining, which has so far has been the main source of income. Significant building in the city center has to be improved in order to support such effort. According to the Master plan for the Tourist City of Sawahlunto, the former housing complex of Pecinan in the Pasar Remaja area is a priority for renovation. The scale of renovation was determined through a survey on the existing building condition and the characteristics of the residents. Based on the results of the survey, the City Planning bureau of Sawahlunto made a Schematic for renovation. This design serves as the reference for the renovation activity. The purpose of this thesis is to find out the willingness of the community to accept the schematic design offered, and to finance the renovation. The modified Contingent Valuation Method (CVM) was used for this purpose, because it can measure the use values as well as the non-use values by creating a hypothetical market value. This value was determined through interviews with the community members about their Willingness to Accept (WTA) and their Willingness to pay (WTP) for the benefits of the renovation. The results show that most residents are willing to accept the renovation plan offered. Their opinions are based on two factors : 1) the economic benefit of living in that area, and 2) their interest, related to historical values, to maintain their land and buildings. However, their willingness to finance the renovation comes to only 30.48 % of the total renovation investment needed. The result of analysis shows that the lack of interest of the residents to finance the renovation is due to the fact that most of their are traders (37.31%) and businessmen (22.39%). They prefer to use their income for the quick yielding short-term investment or getting quick capital return rather than investing for the renovation which may not be enjoyed immediately. Besides the investment preference factor, the residents willingness to pay are also determined bay the amount of investment needed, or the cash flow to be paid monthly, and their preference in judging the schematic design. Based on those factors, the last part of this thesis provides some suggestions to the Local Government of Sawahlunto to formulate approriate financial program for the renovation activity.